Conceptual Framework for Measuring the Reduction of Dust due to Preventive Measures in Infrastructure Construction Projects - Buranasajja, Khomthat; Peansupap, Vachara; Tongthong, Tanit (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Rising PM2.5 levels in Thailand, often exceeding WHO limits, are particularly concerning in the construction industry, a major contributor to dust pollution, especially in infrastructure projects near residential zones. Current assessment methods lack a structured framework and comprehensive data to evaluate dust reduction from control measures in these large-scale projects. This study proposes a framework for evaluating dust reduction through a real-time monitoring system to collect field data. The framework compares PM2.5 values from sensors placed behind protective measures and along the site boundary with theoretical values calculated using an attenuation equation. The difference indicates the reduction in PM2.5 achieved by the control measure. Three sensors were deployed: one at the pollution source, one behind the protective measure, and one to capture background levels. A preliminary study over five working days revealed that, while a 20–40% reduction in PM2.5 levels was anticipated, actual reductions observed during activities like concrete work, steel work, and material handling were generally below 20%. These results, interpreted through the conceptual framework, highlight its ability to capture the limitations of existing control measures under real working conditions. The framework, supported by real-time monitoring tools, enabled consistent assessment across construction phases and effectively reflected the influence of heavy machinery on dust levels. Overall, the findings validate the framework as a structured approach for measuring, analyzing, and interpreting PM2.5 data in infrastructure projects.